Dynamic behavior of reinforced concrete beams under varying rates of concentrated loading - Adhikary, Satadru Das (2012)
The behavior under varying rates of concentrated loading of reinforced concrete (RC) beams was studied, aimed at attaining a better understanding of the effects of loading rates on RC beams. The test program was successful in providing a substantial volume of test data including load vs. mid-span displacement, crack profiles, strain at the mid-point of longitudinal tensile reinforcements and acceleration at several locations along the specimens. Peak load, stiffness, absorption energy and strain rate were found to increase with the enhancement of loading rates. LS-DYNA, an explicit finite element program widely used for three-dimensional nonlinear transient analysis of structures, was employed in this study to provide numerical simulations of RC beams under varying loading rates. Three-dimensional finite element (FE) models of RC beams have been described and verified with the experimental results, followed by a parametric study to investigate the influence of the longitudinal reinforcement ratio, the transverse reinforcement ratio and the shear span to effective depth ratio. Empirical equations are proposed in terms of various parameters to predict the Dynamic Increase Factor (DIF) of maximum resistance of RC beams under varying loading rates.